(untitled) (Indian Journal of Animal Production and Management, 2019)
A bench mark survey was conducted to collect the base line information from the Pantja goat rearers regarding various health management practices of goats under field conditions of Udham Singh Nagar and Nainital districts of Tarai region of the Uttarakhand during a period of two year (April, 2015 to March, 2017). The results of present study revealed that maximum goat rearers (55.81%) followed vaccination practice in the goats while, 44.19 per cent did not adopted this practice. The majorities of goat keepers (70.39%) were well aware towards deworming practices and followed it once or twice in a year. Majority of goat keepers (61.24%) practiced to control ecto- parasites and among them 52.15 per cent practiced manual or indigenous traditional practices used for control of ecto- parasites while; remaining 47.85 per cent used dusting/ spraying (insecticides) method to control external parasites. Overall 95.04 per cent of goat keepers used veterinary/ indigenous traditional practices for the treatment of sick animals. Majority of the respondents (52.87%) informed that they prefer quacks, followed by (27.13%) trained person like veterinary doctors/ livestock inspectors for treatment of their sick and injured animals. Overall data shows that majority of goat keepers (51.94%) reported that availability of veterinary facilities for the treatment of their sick animals was satisfactory followed by (24.65%) good and (23.41%) poor.